We have the rational expression
![\frac{2x^{5}-6x^{2}+4x4y}{2x}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%5E%7B5%7D-6x%5E%7B2%7D%2B4x4y%7D%7B2x%7D%20)
; to simplify it, we are going to try to find a common factor in the numerator, and, if we are luckily, that common factor will get rid of the denominator
![2x](https://tex.z-dn.net/?f=2x)
.
Notice that in the denominator all the numbers are divisible by two, so 2 is part of our common factor; also, all the terms have the variable
![x](https://tex.z-dn.net/?f=x)
, and the least exponent of that variable is 1, so
![x](https://tex.z-dn.net/?f=x)
will be the other part of our common factor. Lets put the two parts of our common factor together to get
![2x](https://tex.z-dn.net/?f=2x)
.
Now that we have our common factor, we can rewrite our numerator as follows:
![\frac{2x(x^{5}-6x+2(2y)}{2x}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%28x%5E%7B5%7D-6x%2B2%282y%29%7D%7B2x%7D%20)
We are luckily, we have
![2x](https://tex.z-dn.net/?f=2x)
in both numerator and denominator, so we can cancel those out:
![x^{5}-6x+2(2y)](https://tex.z-dn.net/?f=x%5E%7B5%7D-6x%2B2%282y%29)
![x^5-6x+4y](https://tex.z-dn.net/?f=x%5E5-6x%2B4y)
We can conclude that the simplified version of our rational function is
![x^{5}-6x+4y](https://tex.z-dn.net/?f=x%5E%7B5%7D-6x%2B4y)
.